DISCURSOS SOBRE A PRÁTICA: O PROCESSO DE FORMAÇÃO DO PROFESSOR DO ENSINO SUPERIOR SEM A FORMAÇÃO PEDAGÓGICA - Vanderlei, Márcia de Oliveira Torres (2012)
This research quested to analyze how universities Professors graduates that do not possess the pedagogical training, rending their academician practices and their trainer route. The target was to identify the representations of the practices from these professors and the impact of habitus on field in its formative process. It was initially considered that these professionals who teach technical subjects, have no specific training (educational) to conduct such classes, but may have inventive teaching practices that were holding during their academic and professional career, and that through them, mediate learning. The methodology option for the development this work was to conduct qualitative research through a questionnaire profile and semi-structured interviews with professors without pedagogical training from two higher education institutions. These tools aim to capture the representation of a group of professors of humanities and Exact on their teaching practices, teacher training and their careers. The author presents the theoretical framework that question issues related to teacher education within higher education with emphasis on: Cunha (2007), Perrenoud (2002), Tardif (2002), Pimenta and Anastasiou (2002) and Nóvoa (1997). For the interviews analyses with the prospect to understanding the representation and the teaching practices, we used part of the theorist framework developed by Pierre Bourdieu, and also the discussion of the instrumental view of Curriculum and pedagogical training. This study enabled us to demonstrate that professors on higher education who participated in this study using a set of techniques, practices, knowledge and behaviors they have learned in specific courses for training teachers, or even pedagogy, especially since not attended. Their development as teachers occurs largely from its past and its coexistence school professional.